She says, he says a pragmatic analysis of the genderlects represented in selected Philippine chick Lliterature - Igloria, Avon Cristta P.; Yanilla-Aquino, Lalaine F. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2009)
For many years, gender, as a social construct, has been of interest in many discourse analytic researches in the academe. It has been the topic of inquiry in disciplines like language studies, communication, literature, and discourse among others. As a contribution to this wide array of sociological and feminist studies, this study focused on the gender differences of women and men, particularly in their conversational styles or genderlects. This study explored the possibility that these differences are present in literary texts, specifically in the discourse of Philippine chick literature.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.